2022
DOI: 10.4081/aiua.2022.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Variant histologies of urothelial carcinoma: Does it change the survival outcomes in patients managed with radical cystectomy?

Abstract: Objective: To investigate the impact of variant histologies (VH) of urothelial carcinoma (UC) on survival outcomes after radical cystectomy (RC). Materials and methods: Data from 181 patients with UC treated with RC between January 2013 and December 2019 at a single tertiary care referral center were retrospectively accessed. All RC specimens were assigned by genitourinary dedicated pathologists. Overall survival (OS), disease-specific survival (DSS) and recurrence-free survival (RFS) were evaluated using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, we can see a tendency that FISH positive patients are more likely to develop UTUC with VH. Given that other studies (31)(32)(33)(34)(35) have denoted that more active treatment is needed in urothelial carcinoma with VH, we need to be more cautious when adopting nephron-sparing surgery for low-risk UTUC with FISH (+), avoiding delaying treatment for some UTUC patients with potentially concomitant VH, although this conclusion cannot be solidly confirmed due to the small sample size of UTUC with VH at present. The drawback of this study exhibits that it is a retrospective study with inevitable bias only based on a single center setting.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, we can see a tendency that FISH positive patients are more likely to develop UTUC with VH. Given that other studies (31)(32)(33)(34)(35) have denoted that more active treatment is needed in urothelial carcinoma with VH, we need to be more cautious when adopting nephron-sparing surgery for low-risk UTUC with FISH (+), avoiding delaying treatment for some UTUC patients with potentially concomitant VH, although this conclusion cannot be solidly confirmed due to the small sample size of UTUC with VH at present. The drawback of this study exhibits that it is a retrospective study with inevitable bias only based on a single center setting.…”
Section: Discussionmentioning
confidence: 98%
“…However, the overall survival rates and the risk of urothelial recurrence in the bladder or contralateral kidney were not affected by the presence of VH. Two recent studies ( 33 , 34 ) have evaluated the different prognostic impact of VH for non muscle-invasive and muscle-invasive bladder cancer, and found that BCG treatment could be proposed considering the need for more intensive oncological surveillance when dealing with the non muscle-invasive with VH. However, clearly associated with features of more aggressive behavior, VH had not any significant impact in survival expectancies after radical cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Sefik et al patients with variant histology were observed to have proportionally higher T stage compared to nonvariant urothelial carcinoma; however there were no significant differences for overall survival and cancer-specific survival (6). A recent study by Pereira et al evidenced that although bladder cancers with histological variants are clearly associated with features of more aggressive behavior, they had not any significant impact in survival expectancies (7). Therefore, the clinical impact of tumor with variant histology on the treatment options still remains under a cloud of doubt in that whether the presence of variant histology justifies an aggressive treatment strategy involving early radical cystectomy (8).…”
Section: Original Papermentioning
confidence: 96%